Durable Peace : Challenges for Peacebuilding in Africa - Matthews, Robert O.; Ali, Taisier Mohamed Ahmed (Book collections on Project MUSE., 2004)
The African continent has been racked with war in the years since decolonization. In the aftermath of violent conflict, peace is often fragile. With Durable Peace, Taisier M. Ali and Robert O. Matthews have brought together leading scholars to discuss the experiences of ten African countries - Angola, Ethiopia, Liberia, Mozambique, Rwanda, Somalia, South Africa, Sudan, Uganda, and Zimbabwe - in recovering from violent civil war. In this series of remarkable and thought-provoking essays, the contributors shed light on the process of peacebuilding. Collectively, they demonstrate that if efforts to restore peace in war-torn societies are to be successful, such efforts must be wide in scope, involving security and political issues, as well as economic development and socio-psychological reconciliation. Additionally, they must be extended over long periods of time and, above all else, anchored in the local community. Peacebuilding is a difficult process, subject to frequent setbacks, and sometimes outright failure. Durable Peace concludes that any peacebuilding effort must include at least four building blocks: a secure environment, new political institutions that are broadly representative, a healthy economy, and a mechanism for dealing with injustices of the past and future. How these blocks are put together will vary, but if they are arranged to fit the specific local circumstances, the outcome will likely be self-sustaining peace.